Hierarchically structured determinants and phaserelated patterns of economic resilience: An empirical case study for European regions - Linus Holtermann; Christian Hundt (Philipps-University Marburg, Department of Geography, 2018)
Our paper seeks to provide empirical evidence for a spatial-temporal system of (short-term) regional resilience determinants. Based on groundwork from Martin (2012) and Martin and Sunley (2015), we employ a nested hierarchy of regional and national determinants to constitute the spatial dimension, while we model the temporal dimension through a resistance and a recovery phase. Utilising hierarchical panel data models for a sample of 22 European countries, we can confirm the presence of a spatial-temporal system as we find significant determinants at both spatial levels that are connected via cross-level interactions and reveal varying, if not opposing directions of influences across the sensitivity and recovery phase.
Keywords: C33; R11; R58; 330; resilience; shocks; resistance and recovery; regional development; regional and national determinants; economic crisis; Europe